Functional Features of the Vocabulary for Color Designation (a Case Study of the Translation of the Andrzej Stasyuk’s Novel “East” ) (Linguostylistic Studies, 2021)
The article analyzes the linguistic features of Andrzej Stasiuk in terms of the stylistic meaning of the lexemes denoting color. A case study material is the translation of the novel “East”. Andrzej Stasiuk is a modern Polish writer, whose prose depicts the real images and real pictures of life, which are often created through sounds, smell, and, especially, color. This distinguishing feature of the author’s style, namely lexemes used for color nomination, has become the subject of this research work.The emphasis is laid on the most productive groups of color names, which became the centers of the artistic image creation manner in the author’s text. The study has revealed that particularly productive are the lexemes related to the green color. In general, we can argue that A. Stasiuk’s prose is ‘green’. It is commonly known that green is the color-symbol of life, youth, and hope. The writer uses it both in direct meaning (in depicting landscapes or even water objects) and figuratively (strengthening the impressions of certain events, the emotional state of the character, as a feature of the character).The study has also identified a high frequency use of the lexeme red, which belongs to the spectrum of hot colors. A. Stasiuk uses it mostly in the direct meaning (describing fire, sunset). Frequently, the epithet red is used to bring some emotional detail to the description in the text, thus, increasing the expressiveness of the whole novel.Significant semantic and stylistic load in the works of A. Stasiuk falls on the adjective black. In the author's text, it is traditionally an attribute of evil, sorrow, and the like.The use frequency of color-lexeme gray is insignificant. The study has revealed its usage in both direct and figurative meaning.There are some examples with such color names as blue, brown, white, gold. They are mostly used in the metaphorical structures and in common word combinations. A small number of examples illustrate a group of words-characteristics: colorful, another color, parti-colored, sandy (all their use cases are in the direct meaning).
Keywords: idiostyle; color names; semantic field; artistic image